Effect Effect of Nutrition Education with Animated Video on Knowledge and Attitude of Toddler Mothers in Bangkok Village, Glagah District, Lamongan Regency - Faradila, Talita Arina (Jurnal Gizi dan Kesehatan Nusantara, 2024)
The growth and development of toddlers is greatly influenced by good nutritional intake. However, mothers’ lack of knowledge and attitudes towards toddler nutrition is often the main obstacle in meeting children’s nutritional needs. This research aims to determine the effect of nutrition education using animated video media on increasing the knowledge and attitudes of mothers of toddlers in Bangkok Village, Glagah District, Lamongan Regency. This research used a Quasi Experimental design with a pretest-posttest control group design. The research sample consisted of 40 mothers of toddlers who were divided into an experimental group and a control group. Nutrition education was provided using animated video media to the experimental group, while the control group received education through lectures. Data was collected through knowledge tests and attitude questionnaires before and after the intervention. Data analysis was carried out using the Mann Whitney test. The research results showed a significant increase in the knowledge and attitudes of mothers of toddlers in the experimental group after being given nutrition education with animated videos. The average value of knowledge increased by 12.2%, and attitude increased by 15.4%. Education using animated videos has proven to be more effective than the lecture method in increasing the knowledge and attitudes of mothers of toddlers regarding nutrition.